Dynamic corporate risk management: Motivations and real implications - Dionne, Georges; Gueyie, Jean-Pierre; Mnasri, Mohamed (Journal of Banking & Finance, 2018)
We investigate the dynamics of corporate hedging programs used by US oil producers and examine the effects of hedging maturity choice on firm value. We find evidence of a concave relationship between hedging maturity and the likelihood of financial distress and oil spot prices. We further investigate the motivations of the early termination of outstanding hedging contracts. Using the essential heterogeneity approach, we evaluate the causal effects of hedging maturity on firm value. Marginal firm value increases with short-term hedging maturity. The causal effects vary across oil producers with different hidden attributes.